Acute effects of static stretching and massage on flexibility and jumping performance - Yildiz, Suat (J Musculoskelet Neuronal Interact, 2020)
OBJECTIVE: The purpose of this study was to evaluate the effects of static stretching and the application of massage on flexibility and jump performance. METHODS: Thirty-five athletes studying Physical Education at University (mean age 23.6±1.3 years, mean height 177.8±6.3 cm and mean weight 72.2±6.7 kg) performed one of three different warm-up protocols on non-consecutive days. Protocols included static stretching [SS], combined static stretching and massage [SSM], and neither stretching nor massage [CONT]. The athletes performed flexibility, countermovement jump (CMJ) and squat jump (SJ) tests. RESULTS: SS and SSM protocols demonstrated 12% (p<0.05) and 16% (p<0.05) respectively greater flexibility than the CONT protocol. SJ and CMJ performances were significantly decreased 10.4% (p<0.05) and 5.5% (p<0.05) respectively after the SS protocol. There was no significant difference between SSM and CONT protocol in terms of SJ and CMJ performance. CONCLUSION: This research indicates that whereas static stretching increases the flexibility it decreases the jumping performance of the athletes. On the other hand, the application of massage immediately following static stretching increases flexibility but does not reduce jumping performance. Considering the known negative acute effects of static stretching on performance, the application of massage is thought to be beneficial in alleviating such effects.